(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The ATLAS Network was established by law enforcement special intervention units of the EU Member States and associated countries. All units who are part of this network are ready to respond to critical events and situations at any time when European security is at risk. The network is based at the Europol headquarters within the European Counter Terrorism Centre since 2018. It is continuously supported internally and directly connected to other networks in the law enforcement sector as well as other EU agencies. The subject of this study is the security of the European Union. The aim of this study is to reveal the possibilities for using the capabilities of the Atlas network to improve the security of the European Union. Based on the analyses conducted, some conclusions are drawn at the end of the article.